INSTRUMENTS FOR ECONOMIC REVENUE OF ENTERPRISES IN THE CONDITIONS OF TRANSFORMATION - SHANDOVA, Nataliia; DEZHKUNOV, Yuri; YAKOVLIEV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article forms a definition of the process of economic renewal, which makes it possible to consider economic renewal as a multicomponent process that includes not only innovation and modernisation, but also cultural adaptation and development of social capital. The key aspects of the process of economic renewal are identified and substantiated, which include, innovative development, digitalisation, green technologies, modernisation of management practices, human potential development, global integration and adaptation to changes. The reasons that make the aspects of the economic renewal process particularly relevant for domestic enterprises are considered, which emphasises the need to adapt to global trends while maintaining local specifics.To ensure the effectiveness of economic renewal processes, the principles of economic renewal have been developed, the application of which will facilitate the integration of key aspects of the economic renewal process, identify strategies that will allow enterprises to adapt to new conditions, maximise the use of available resources and achieve sustainable development. The methodological basis of the developed principles is systemic, integrative, institutional, practical, comparative and human-centred approaches, which allowed to build a comprehensive structure of principles that can integrate innovative, managerial and social aspects of economic renewal. The proposed set of principles for economic renewal includes a group of universal approaches that are fundamental to the renewal of economic systems that adapt to the requirements of the global market and a group of specific principles that consider the specifics of the national regulatory and economic environment, local conditions and post-crisis recovery needs. The combination of universal and specific approaches creates a balanced, adaptive and effective approach to the transformation of economic systems, which, in the form of a flexible and adaptive toolkit for enterprise management, allows solving specific problems without losing touch with global goals, ensuring sustainable development in the face of uncertainty and crisis.
Keywords: economic renewal; principles of economic renewal; enterprises; sustainable development; tools; transformation; competitiveness